Leaf anatomy and micromorphology of selected plant species in coastal area of Kuantan, Pahang, Malaysia - Che Amri, Che Nurul Aini; Mohammad Mokhtar, Nurul Atiqah; Shahari, Rozilawati (Zibeline International, 2019)
Plant anatomy can play vital role in plant taxonomy for successfully resolve taxonomic problems among different plant species. The anatomical studies of plant species living in coastal area of Kuantan, Pahang are scarce. Thus, the aim of this study was to identify the common, variation and diagnostic characteristics of leaf anatomy and micromorphology of selected plant species collected from Balok and Sepat beach area which can give additional information for identification of species. Four species studied namely Ipomoea pes-caprae (L.) R. Br., Calophyllum inophyllum L., Hibiscus tiliaceus L. and Stachytarpheta jamaicensis (L.) Vahl. Methods used were sectioning using sliding microtome, epidermal peeling and leaf micromorphology method using scanning electron microscope (SEM). The findings from this study showed that only three characteristics are similar among them which include the presence of collenchyma, sclerenchyma and mucilage cells or canals in either petiole or midrib of the leaves. Meanwhile, there are eight differences were observed which are types of stomata and trichomes, pattern of anticlinal wall and vascular bundles, type of epicuticular wax structures, cuticle ornamentations, size of epidermal cells and the presence of cell inclusions. The diagnostic characteristics identified in this study are closed-system of vascular bundle, presence of multicellular capitate glandular, 2-4 armed trichomes and 5-8 armed stellate trichomes and also flakes type of wax layers that can only be found in H. tiliaceus while 1:1 ratio size of epidermal cells can only be found in I. pes-caprae. The study reveals that leaf anatomy and micromorphology characteristics could be beneficial as an additional data for identification of species along the coastal area of Kuantan, Pahang.